Sustaining Water-Related Heritage Infrastructures as Part of An Integrated Water Resource Management Program - Radianta Triatmadja; Djoko Legono; Budi Wignyosukarto; Fatchan Nurrochmad; Sunjoto Sunjoto (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
The history of the water resources development in the world is generally inspired by the physical, climate and socioenvironment conditions such as geographical, culture and civilization at the local level. For many years, humans have spent tremendous efforts and time improving the quality of life through adequate water utilization. This research, therefore, aims to analyze the ancient water-related infrastructures as cultural heritages in creating a functional and adequate design. Data were obtained from the Mataram Canal in Yogyakarta Province which was selected due to the success story and various benefits associated with the Indonesian history of water resources in Central Java provinces. Today, some places along the canal have become tourist destinations, and it is more popular in Yogyakarta due to its architectural history. However, the diversification of water utilization in fishery ponds along the canal and the shift in land utilization from rice field to housings, and government buildings may undermine the function of the canal. The factual condition associated with the periodic decrease in irrigation command does not make the Mataram Canal useless. Therefore, efforts to maintain its function through restoration, and revitalization, can enhance water supply for irrigation and other purposes such as fish ponds and, pollutant dilution. The Strength-Weakness-Opportunity-Threat (SWOT) method with some key performance indicators was adopted to access the necessity of the sustainability program of the Mataram Canal as the heritage infrastructure. Some key performance indicators related to Integrated Water Resources Management (IWRM) program in Indonesia were introduced and utilized to prioritize the necessary actions. The results showed that the SWOT analysis promotes various actions to support the IWRM-related program of Mataram Canal. Furthermore, the implementation of the promoted actions would contribute to the longer sustainability of the Mataram Canal.